Aprimoramento metodológico da técnica de plastinacão nas plumagens de aves: uma perspectiva estético-científica - Silva, Marcos Vinícius Freitas (2024)
Plastination is considered the gold standard technique in the preservation of biological tissues, allowing for their conservation in a natural, non-toxic manner, with easy storage and high durability. However, the literature on bird plastination is scarce due to the complexity of feather treatment. Since birds are the second most diverse class among vertebrates, it is essential to document and preserve their diversity in collections through modern techniques. This study aimed to investigate and adapt the plastination process for bird plumage, preserving the morphological integrity and natural appearance of the specimens. Thirty-two carcasses of Domestic Pigeon (Columba livia) were used as a model, plastinated according to two impregnation protocols: at room temperature (±25 °C) and at low temperature (-25 °C). After impregnation, four treatments were applied, each with 6 specimens, under the two impregnation protocols: adsorption with starch, absorption with paper, heating (60 °C), and emulsification. Macro and microscopic analyses assessed the structural changes caused by the silicone and the effectiveness of the treatments. Additionally, the mass of the specimens was measured before and after the treatments to evaluate the effectiveness of silicone removal at the end of the process. The treatments that showed promising results were absorption with paper and adsorption with cornstarch; these demonstrated a significant visual aesthetic improvement, with effective removal of excess silicone from the feathers, while the other treatments did not produce promising aesthetic results. However, microscopically, although cornstarch removed much of the silicone from the surface of the feathers, it produced artifacts adhered to this surface, while the other treatments resulted in the formation of a silicone layer on the feather’s barbs. These results were extremely important for understanding the effect of plastination on feather structure, allowing the technique to be adapted for birds, expanding its use in educational and scientific collections, exhibition classes, and research. Furthermore, both treatments offer an economic and ecological solution for long-term collection management, contributing to the preservation of specimens with the highest quality when compared to the conventional plastination protocol. Finally, this study helped solve a problem that has challenged plastination since 1978, which is the plastination of birds with the natural preservation of feathers, aiding in the dissemination and application of the plastination technique to this highly diverse taxon.